Enhancing English Literacy through Ethnopedagogy: A Focus on Cultural Relevance in Teaching Practices - Gumartifa, Asti; Sofendi, Sofendi; Mirizon, Soni (Universitas Pendidikan Mandalika, 2025)
Information and Communication Technology (ICT) provides digital media innovations to gain Literacy and understanding. In South Sumatra, the potential of local wisdom, such as folklore and traditional songs, highlights the importance of these elements in Ethnopedagogy and cultural preservation. The research provides contributions to both educators and learners. By incooperating ethnopedagogy into the learning materials, it can make teaching practice become more inclusive and enhance literacy in a culturally contextualized manner optimally. Therefore this study aims to enhance students’ English literacy by integrating Ethnopedagogy context throuh learning material, which emphasizes cultural relevance and teaching practices that also reflect students' cultural backgrounds. This study employs a descriptive qualitative methodology to explore the enhancement of English literacy through Ethnopedagogy. Data were collected through a literature review. The qualitative approach facilitated an in-depth analysis of how cultural relevance and effective teaching practices can improve English literacy education. This study investigates the integration of cultural contexts into Literacy Instruction. The study then addresses the role of cultural identity in literacy achievement. The research further explores challenges and solutions in culturally relevant literacy instruction. The findings underscore the significance of incorporating local wisdom and cultural elements in developing effective English literacy programs that resonate with students' cultural backgrounds and enhance their learning experiences.